Structure and Expression Analysis of Sucrose Phosphate Synthase, Sucrose Synthase and Invertase Gene Families in Solanum lycopersicum - Duan, Yaoke (Int J Mol Sci, 2021)
Sucrose phosphate synthase (SPS), sucrose synthase (SUS) and invertase (INV) are all encoded by multigene families. In tomato (Solanum lycopersicum), a comprehensive analysis of structure characteristics of these family genes is still lacking, and the functions of individual isoforms of these families are mostly unclear under stress. Here, the structure characteristics of the three families in tomato were analyzed; moreover, as a first step toward understanding the functions of isoforms of these proteins under stress, the tissue expression pattern and stress response of these genes were also investigated. The results showed that four SPS genes, six SUS genes and nineteen INV genes were identified in tomato. The subfamily differentiation of SlSPS and SlSUS might have completed before the split of monocotyledons and dicotyledons. The conserved motifs were mostly consistent within each protein family/subfamily. These genes demonstrated differential expressions among family members and tissues, and in response to polyethylene glycerol, NaCl, H(2)O(2), abscisic acid or salicylic acid treatment. Our results suggest that each isoform of these families may have different functions in different tissues and under environmental stimuli. SlSPS1, SlSPS3, SlSUS1, SlSUS3, SlSUS4, SlINVAN5 and SlINVAN7 demonstrated consistent expression responses and may be the major genes responding to exogenous stimuli.